Micropatterned Elastomeric Composites for Encapsulation of Transient Electronics - Han, Won Bae; Ko, Gwan-Jin; Yang, Seung Min; Kang, Heeseok; Lee, Joong Hoon; Shin, Jeong-Woong; Jang, Tae-Min; Han, Sungkeun; Kim, Dong-Je; Lim, Jun Hyeon; Rajaram, Kaveti; Bandodkar, Amay Jairaj; et al. (American Chemical Society, 2023)
Although biodegradable, transientelectronic devicesmust dissolveor decompose via environmental factors, an effective waterproofingor encapsulation system is essential for reliable, durable operationfor a desired period of time. Existing protection approaches use multipleor alternate layers of electrically inactive organic/inorganic elementscombined with polymers; however, their high mechanical stiffness isnot suitable for soft, time-dynamic biological tissues/skins/organs.Here, we introduce a stretchable, bioresorbable encapsulant usingnanoparticle-incorporated elastomeric composites with modificationsof surface morphology. Nature-inspired micropatterns reduce the diffusionarea for water molecules, and embedded nanoparticles impede waterpermeation, which synergistically enhances the water-barrier performance.Empirical and theoretical evaluations validate the encapsulation mechanismsunder strains. Demonstration of a soft, degradable shield with anoptical component under a biological solution highlights the potentialapplicability of the proposed encapsulation strategy.